SIMRS Fraud Against INA-CBGs/INA-DRG in the Implementation of KRIS in Hospitals - Andi Yaumil Bay R Thaifur; Reski Dewi Pratiwi; Afriyana Amelia Nuryadin; Mangindara (Universitas Muhammadiyah Palu, 2026)
Hospital Management Information Systems (SIMRS) serve as a critical foundation for ensuring the accuracy of National Health Insurance (JKN) claims under the Indonesian Case Based Groups (INA-CBGs/INA-DRG) payment system. However, limited SIMRS integration quality combined with the policy shift toward Standard Inpatient Class (KRIS) implementation pursuant to Presidential Regulation No. 59 of 2024 potentially increases the risk of data conflicts and claim fraud in hospitals. This systematic literature review aimed to examine the role of SIMRS in potential fraud within INA-CBGs/INA-DRG claims during KRIS implementation. A systematic literature review using descriptive qualitative analysis was conducted across PubMed/Medline, ScienceDirect, Wiley Online Library, Cochrane Library, and Google Scholar. From 205 initially identified articles, five primary studies were included. Significant weaknesses were found in SIMRS integration, data quality, and claim verification that increased fraud risk. BPJS Kesehatan data indicated potential fraud amounting to IDR 866.8 billion was successfully prevented in 2023. A negative tariff disparity averaging IDR 3,036,855.37 (36.66%) was identified for Caesarean section cases. Fingerprint-based verification technology reduced fraud to 0.01% in one facility. An integrated and reliable SIMRS supported by verification technology plays a strategic role in preventing INA-CBGs/INA-DRG claim fraud and supporting effective KRIS implementation.